COVID-19 – a new challenge for the medical community - Valančius , D.; Kasiulevičius , V. (Neurologijos seminarai, 2020)
Coronaviruses are important human and animal pathogens. At the end of 2019, a novel coronavirus was identified as the cause of a cluster of pneumonia cases in Wuhan, a city in the Hubei Province of China. It rapidly spread resulting in an epidemic throughout China followed by an increasing number of cases in other countries through out the world. The virus that causes COVID-19 is designated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Understanding of COVID-19 is evolving. This article discusses the virology, epidemiology, clinical features, diagnosis, and prevention of COVID-19 and other coronaviruses.
Keywords: coronaviruses; SARS-CoV-2; COVID-19